UPAYA INGO (INTERNATIONAL NON-GOVERMENTAL ORGANIZATION) DALAM AKTIFITAS PEACEBUILDING DI SIPRUS TAHUN 2008-2014 - Zikron, Muhamad; Saeri, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This reserach will discusse about effort of Non-Government Organization PeacePlayer International in Cyprus, 2008-2014 .Cyprus until now still hit by conflict and secession. Conflict in the Republic of Cyprus is from 13 new amendments proposed by the President of the Republic of Cyprus. This amendment was rejected by the representative of the President of the Republic of Cyprus as it is considered detrimental to the ethnic Turkish and manufacture without involving the vice president. Conflicts two leaders then have an impact on society and the parliament of the Republic of Cyprus. violence in almost every city in the Republic of Cyprus, the presence of organizations that represent each ethnic Greek and Turkish involvement and further aggravate the security situation in Cyprus, so in 1983 the ethnic Turkish declare independence. This independence is not recognized by the international community. This research use the perspective of pularalism with two-track diplomacy theory supported by the concept of peacebuilding and international organization. In the case of Cyprus non-government ornagization PeacePlayer International act as third party actor bridging dialoge between communities at the grassroots level. This NGO is only in charge of post-conflict situations and assisting intergovernmental agreement. Keyword: Peacebuilding, Greek Cypriot, Turkish Cypriot, Peaceplayer International